The War of American Independence, 1763-1783 - Carpenter, Stanley D. M., author.
1 online resource.
Keywords: "The War of American Independence, 1763-1783: Falling Dominoes addresses the military, maritime and naval, economic, key personalities, key societal groups, political, imperial rivalry, and diplomatic dynamics and events from the post-Seven Years' War era in Great Britain's North American colonies through the end of the War of American Independence. Beginning in 1763 and moving through the War chronologically, the authors argue that British political and strategic leaders failed to develop an effective strategy to quell the discontent and subsequent revolt in the North American colonies and thus failed to restore allegiance to the Crown. This book describes and analyzes events and the outcomes of central players' decisions - the British North American colonies, Great Britain, France, Spain, and the Dutch Republic - and the resultant actions. It examines events through the thematic lens of strategy, political and military leadership, public attitudes, economics, international rivalries and relations, and the role of traditionally less-considered groups: women, slaves, and Native American peoples. An enlightening and essential read for all history students, from high school through to those on postgraduate courses, as well as those with an interest in American Independence history"--